Human Resource Management, Digital Transformation, and Sustainable Business for SMEs Growth with Market Adaptation - Andry Roy PS; Minasari Nasution, (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study examines the impact of human resource management (HRM), digital transformation, and sustainable business practices on the growth of culinary and coffee small and medium enterprises (SMEs) in Balige, with market adaptation as a moderating variable. A quantitative method was applied using structured questionnaires distributed to SME owners and managers. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results demonstrate that HRM, digital transformation, and sustainability significantly enhance SME growth, while market adaptation strengthens these relationships. R² and Q² values confirm strong explanatory and predictive power. This research contributes theoretically by integrating HRM and sustainability perspectives into SME growth literature and provides practical implications for SMEs to adopt digital and adaptive strategies in a competitive market.